Promoting Gender Equity in Education to Ensure Equal Opportunities and Inclusive Learning Environments - Kazuhiro Saito Yuma (PT. Islamic Research Publisher, 2025)
This study explores strategies to promote gender equity in education, aiming to ensure equal opportunities and foster inclusive learning environments. Gender disparities in education remain a persistent challenge, affecting students’ access to resources, participation in classroom activities, and achievement outcomes. Employing a qualitative research design, data were collected through semi-structured interviews, focus group discussions, and document analysis involving educators, policymakers, and students across primary, secondary, and tertiary educational institutions. The analysis reveals that gender biases are embedded not only in curricular content and teaching practices but also in institutional policies and cultural perceptions of gender roles. Targeted interventions, such as gender-sensitive pedagogy, inclusive policy frameworks, and teacher professional development programs, significantly enhance equitable participation and foster supportive learning environments. Furthermore, active engagement from school leadership, parents, and community stakeholders is critical in sustaining long-term gender equity initiatives. This study underscores the importance of integrating policy, pedagogy, and community action to address structural and socio-cultural barriers to equality. The findings contribute to the body of knowledge on inclusive education by providing empirical evidence of effective strategies to reduce gender disparities and promote equitable learning opportunities. In addition, the study offers practical recommendations for educators, policymakers, and researchers, emphasizing the need for continuous monitoring, gender-awareness training, and collaborative efforts to achieve sustainable gender equity in education. Ultimately, this research advocates for systemic, transformative approaches that enable all learners, regardless of gender, to thrive in equitable, inclusive educational settings.